Desempeño del discurso narrativo en la producción de narraciones en niños de 5 años de una institución educativa nacional ubicada de la ciudad de Chiclayo, Arequipa y Pucallpa - Tafur Villacorta, Vivian Mayte (2024)
The present research arises from the need to provide data on Narrative Discourse Performance in children in our country. Therefore, the purpose of this study was to determine if there are discrepancies in the "stages" and "levels" of Narrative Discourse Performance in 5-year-old children attending initial level in the cities of Arequipa, Chiclayo, and Pucallpa in 2023. The investigation was conducted under a quantitative approach using a non-experimental, cross-sectional, descriptive-comparative design. The sample consisted of 134 children aged 5 years 0 months to 5 years 11 months from the mentioned cities. To carry out the research, the Evaluation of Narrative Discourse (EDNA) by authors Pavez, Maggiolo, and Coloma (2008), adapted and standardized in Peru in 2013 by Cucho and Roque, was applied. The data reflected that there were no statistically significant differences in the performance of narrative production "stages" among the three cities. However, statistically significant discrepancies were found in the performance of narrative production "levels". Finally, in the overall sample, it was evident that children achieved a higher percentage in the "structured stage" and "level 6" of narrative performance in productions, thus reflecting a performance within the "average" and "below average" range. Keywords: Performance, Narrative Discourse, stages, levels, Arequipa, Chiclayo, Pucallpa.